1992
DOI: 10.1111/j.2044-8260.1992.tb00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and psychiatric abnormalities in myalgic encephalomyelitis: A preliminary report

Abstract: Ten patients attending one general medical hospital clinic who fulfilled operational criteria for the diagnosis of myalgic encephalomyelitis (ME) and with a history longer than three months, underwent a series of standardized neuropsychological and psychiatric tests. Nine were able to complete the tests and were individually matched with a normal control group for age, sex, educational background and premorbid intelligence. The ME subjects showed inferior performance to the controls on two tests of verbal memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2

Year Published

1993
1993
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 13 publications
1
23
2
Order By: Relevance
“…Smith (1991) found that CFS patients were slower at psychomotor tasks, had problems with selective and sustained attention, certain memory impairments and also increased sensitivity to visually disturbing patterns. In contrast to this, Riccio, Thompson, Wilson, Morgan & Lant (1992) reported that their CFS patients were only impaired on the ability to recall information from a story and on a paired associate learning task. The main aim of the present study was to extend these preliminary studies using a larger, clearly defined group of CFS patients.…”
mentioning
confidence: 84%
“…Smith (1991) found that CFS patients were slower at psychomotor tasks, had problems with selective and sustained attention, certain memory impairments and also increased sensitivity to visually disturbing patterns. In contrast to this, Riccio, Thompson, Wilson, Morgan & Lant (1992) reported that their CFS patients were only impaired on the ability to recall information from a story and on a paired associate learning task. The main aim of the present study was to extend these preliminary studies using a larger, clearly defined group of CFS patients.…”
mentioning
confidence: 84%
“…For example, Riccio et al (1992) compared the performance of nine CFS patients to nine control subjects matched for age, sex, and premorbid intelligence. They employed a series of neuropsychological tests measuring intelligence, memory, problem solving, and psychomotor speed.…”
Section: Studies Employing Control Groupsmentioning
confidence: 99%
“…For example, patients with CFS report an increased perception of muscular effort despite submaximal performance on exercise testing (Stokes et al 1988 ;Riley et al 1990), but the same may be true in depression, where impairment of motor function extends even to maximal voluntary hand grip (Cohen et al 1982 ;Moffoot et al 1994). Subjective reports of cognitive impairment in CFS are supported by objective evidence for slowed reaction time and poor memory or attention (Millon et al 1989 ;Altay et al 1990 ;Riccio et al 1992 ;Grafman et al 1993 ;MacDonald et al 1993 ;Ray et al 1993 ;Sandman et al 1993 ;Schmaling et al 1994 ;Cope et al 1995 ;DeLuca et al 1995 ;Joyce et al 1996 ;Marcel et al 1996 ;Marshall et al 1997 ;Vollmer-Conna et al 1997 ;Wearden & Appleby, 1997 ;Johnson et al 1998). A comparison with depression suggests a similar pattern of impairments (e.g.…”
Section: Introductionmentioning
confidence: 99%